The Role of INAPERTURATE POLLEN1 as a Pollen Aperture Factor Is Conserved in the Basal Eudicot Eschscholzia californica (Papaveraceae) - Mazuecos-Aguilera, Ismael; Romero-García, Ana Teresa; Klodová, Božena; Honys, David; Fernández-Fernández, María C.; Ben-Menni Schuler, Samira; Dobritsa, Anna A.; Suárez-Santiago, Víctor N. (Frontiers in Plant Science, 2021)
Pollen grains show an enormous variety of aperture systems. What genes are involved in the aperture formation pathway and how conserved this pathway is in angiosperms remains largely unknown. INAPERTURATE POLLEN1 (INP1) encodes a protein of unknown function, essential for aperture formation in Arabidopsis, rice and maize. Yet, because INP1 sequences are quite divergent, it is unclear if their function is conserved across angiosperms. Here, we conducted a functional study of the INP1 orthologue from the basal eudicot Eschscholzia californica (EcINP1) using expression analyses, virus-induced gene silencing, pollen germination assay, and transcriptomics. We found that EcINP1 expression peaks at the tetrad stage of pollen development, consistent with its role in aperture formation, which occurs at that stage, and showed, via gene silencing, that the role of INP1 as an important aperture factor extends to basal eudicots. Using germination assays, we demonstrated that, in Eschscholzia, apertures are dispensable for pollen germination. Our comparative transcriptome analysis of wild-type and silenced plants identified over 900 differentially expressed genes, many of them potential candidates for the aperture pathway. Our study substantiates the importance of INP1 homologues for aperture formation across angiosperms and opens up new avenues for functional studies of other aperture candidate genes.